Demonstration of a System Identification on Real Step-Down Power Converters - Peter Drgona; Rastislav Stefun; Slavomir Kascak; Jan Morgos (Communications - Scientific letters of the University of Zilina, 2020)
System identification is a scientific field with a wide range of applications, including transport and transportation systems. Automotive industry has a growing trend of power converters implementation. In addition, intelligence of converters is developing. Thus, the power electronics and autotronics are application areas where identification can also be applied. Since buck (step-down), boost (step-up) and buck-boost are the most common topologies of the converters in automobiles, this article aims to demonstrate possibilities of using the identification procedure on the synchronous buck converter. The objective is to obtain a parametric model that could be further useful in analysis and other work with the converter.